2017
DOI: 10.1371/journal.pone.0179207
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, clinical course, and outcomes of homeless and non-homeless patients admitted to ICU: A retrospective cohort study

Abstract: BackgroundLittle is known about homeless patients in intensive care units (ICUs).ObjectivesTo compare clinical characteristics, treatments, and outcomes of homeless to non-homeless patients admitted to four ICUs in a large inner-city academic hospital.Methods63 randomly-selected homeless compared to 63 age-, sex-, and admitting-ICU-matched non-homeless patients.ResultsCompared to matched non-homeless, homeless patients (average age 48±12 years, 90% male, 87% admitted by ambulance, 56% mechanically ventilated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
(19 reference statements)
1
10
1
4
Order By: Relevance
“…In the current study, about two‐thirds of patients involved in the reported errors exhibited low health literacy, communication difficulties or isolation. This finding reflects the general characteristics of patients in ICUs (Ostermann et al, ; Smith et al, ). Further, these patients, compared with other patients, are unstable, require more complicated nursing care and cannot protect themselves (Beccaria et al, ; Garrouste‐Orgeas et al, ; Wittich et al, ).…”
Section: Discussionsupporting
confidence: 59%
“…In the current study, about two‐thirds of patients involved in the reported errors exhibited low health literacy, communication difficulties or isolation. This finding reflects the general characteristics of patients in ICUs (Ostermann et al, ; Smith et al, ). Further, these patients, compared with other patients, are unstable, require more complicated nursing care and cannot protect themselves (Beccaria et al, ; Garrouste‐Orgeas et al, ; Wittich et al, ).…”
Section: Discussionsupporting
confidence: 59%
“…Pneumonia has a particularly strong impact on vulnerable populations. CAP is frequent among refugees [10], the homeless [11][12][13][14], drug users [15,16] and people of low socioeconomic status [17] and is associated with increased mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the type and number of organ failures have not been reported in other studies of homeless ICU admissions [ 8 , 9 ] or contemporary population-level studies of ICU admissions in the general US population, precluding direct comparisons of severity, as traditional severity of illness scores could not be derived from administrative data. However, recent reports of ICU admissions of the homeless described patients with much higher severity of illness than in our cohort, as judged by the higher use of mechanical ventilation (44% [ 8 ] and 56% [ 9 ]) and high mortality (20.8% [ 8 ] and 29% [ 9 ]). The difference likely represents a combination of both local practice patterns at study hospitals and lower availability of ICU beds outside the US [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, data on critically ill homeless patients remain sparse. Two recent studies from France [ 8 ] and Canada [ 9 ] described high severity of illness, resource utilization, and hospital mortality of ICU-managed homeless patients. However, these studies were limited by small cohort size and examination of single-center data.…”
Section: Introductionmentioning
confidence: 99%